BENTUK-BENTUK PREPOSISI DALAM SKRIPSI MAHASISWA PROGRAM STUDI TEKNIK LINGKUNGAN FAKULTAS TEKNIK UNIVERSITAS BATANGHARI - Supriyati Supriyati; Nurhasanah Nurhasanah (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research aims to describe the classification of preposition forms contained in the thesis of the Student of Environmental Engineering Study Program, Faculty of Engineering, Batanghari University (A Case Study of Sunela Thesis). The method used in this research is qualitative descriptive. The data in the research is in the form of sentence citations containing prepositions. The source of data is in the form of documents in the form of a thesis Sunela Student of  Environmental Engineering Study Program Faculty of Engineering Batanghari University. The data collection technique used is documentation. Data analysis was conducted by using Chaer theory related to the use of prepositions. The results of the research found that there are nine preposition groups contained in Sunela's thesis. The nine preposition groups are preposition that state existence,  the direction of origin,  the direction of purpose, the perpetrator, tools,  comparisons,  things or problems and  the consequences and prepositions that state the purpose. In this research, the researcher concluded that the more dominant quotation found was a preposition that noted the existence according to Sunela's communicative thesis's substance.